Ozonation of ofloxacin in water: By-products, degradation pathway and ecotoxicity assessment - Tay, K.S.; Madehi, N. (Elsevier, 2015)
Application of ozonation in water treatment involves complex oxidation pathways that could lead to the formation of various by-products, some of which may be harmful to living organisms. In this work, ozonation by-products of ofloxacin (OFX), a frequently detected pharmaceutical pollutant in the environment, were identified and their ecotoxicity was estimated using the Ecological Structure Activity Relationships (ECOSAR) computer program.In order to examine the role of ozone (O3) and hydroxyl radicals (OH) in the degradation of ofloxacin, ozonation was performed at pH2, 7 and 12. In this study, 12 new structures have been proposed for the ozonation by-products detected during the ozonation of ofloxacin. According to the identified ozonation by-products, O3 and OH were found to react with ofloxacin during ozonation. The reaction between ofloxacin and O3 proceeded via hydroxylation and breakdown of heterocyclic ring with unsaturated double-bond. The reaction between ofloxacin and OH generated various by-products derived from the breakdown of heterocyclic ring. Ecotoxicity assessment indicated that ozonation of OFX could yield by-products of greater toxicity compared with parent compounds.